Anatomy of the olfactory bulb in Greenland shark Somniosus microcephalus (Bloch & Schneider, 1801). (8th February 2017) - Ferrando, S.; Gallus, L.; Ghigliotti, L.; Vacchi, M.; Amaroli, A.; Nielsen, J.; Christiansen, J. S.; Pisano, E.
Summary: Gross morphology and histology of the olfactory rosette of Greenland shark Somniosus microcephalus (Bloch & Schneider, 1801), suggest a well‐developed olfactory capability for this top predator and scavenger native to Arctic waters. In the present paper, observations on the olfactory rosette are reported together with the gross morphology and histology of the olfactory bulb whereby the histological analyses revealed some peculiar traits. The olfactory bulb is macroscopically divided into two sub‐bulbs and a central undivided part that contain the layers typical of olfactory bulb histology. The two visible sub‐bulbs are actually bundles of fila olfactoria. In addition, the olfactory lateral ventricle is peculiarly branched, which may increase the ependymal surface or, alternatively, decrease the distance between the tissues of the olfactory bulb and the ventricle itself. The ependymal surface is known to be a proliferative zone in the olfactory bulb of fishes. In Greenland shark, the olfactory epithelium showed frequent mitosis and apoptosis highlighting the importance of this site in cell renewal. This issue should be pursued further to gain a deeper understanding of the sensory biology of Greenland shark and of elasmobranchs in general.